The Meta-Problem in Scientific Research in Physical Education and Sport: Architecture and Pathways to Knowledge - Khudolii, Oleg; Ivashchenko, Olha; Khudolii, Mykola (Physical Education Theory and Methodology, 2026)
Purpose. To systematize approaches to understanding the meta-problem and its operationalization in research on physical education and sport. Materials and Methods. The study was conducted as a theoretical-methodological analysis with elements of retrospective empirical verification. The logic of the work was based on the assumption that productive research programs are formed not only around local hypotheses, but around higher-order concepts that determine research architecture, sequence of proof, and pathways to new knowledge. Conceptual analysis, comparative methodological synthesis, and retrospective examination of completed doctoral studies devoted to modeling learning, training, and motor development processes were applied. Results. The meta-problem was interpreted as a higher-level conceptual construct preceding the formulation of topic, aim, hypothesis, and methods. It determines the framework within which these elements acquire coherence and scientific meaning. It was shown that in physical education and sport, learning, upbringing, and training may be interpreted as derivative forms of a unified process of detecting deviations from a functionally optimal mode and correcting them. The central contradiction of development lies in the need to change while preserving functional stability. Under conditions of local and limited positive factor effects, classical two-group designs have restricted explanatory value, whereas factorial designs, repeated measurements, and response-surface approaches are more productive for identifying optimal regimes. Conclusions. The meta-problem should be considered as a methodological level organizing the critical path of scientific inquiry. Its practical value lies in improving research design, manuscript evaluation, and the production of cumulative scientific knowledge.